PRODUÇÃO DE PAINEL COMPENSADO PARA USO EXTERIOR COM MADEIRAS DE PARICÁ E EMBAÚBA - Machado, João Fábio (2016)
This study aimed to assess the technical feasibility of using wood paricá (Schizolobium amazonicum Huber ex. Ducke) and embaúba (Cecropia palmata Willd.) for veneer and plywood for external use, using two types of adhesives and different wood veneer compositions. Paricá and embaúba trees were collected in a forest area planted from clearing enrichment in the municipality of Dom Eliseu in the Pará state. The pinus veneer were donated by a company in the municipality of Irati, Paraná State. It was determined the wood basic density by means of the standard NBR11941 / 2003, the yield was evaluated paricá and embaúba species lamination and the veneer quality of the three species by means of the standards classification of hardwood and coniferous plywood panels (NBR / ABNT 2426 (2006). The panels, with dimensions (60x60cm), were produced in the laboratory and used pure wood of three kinds, and two combinations of the paricá and embaúba species, totaling five compositions glued with adhesives, phenolformaldehyde (FF) with 35.3% solids, tannin-formaldehyde (TF) with 43.9% solids and a weight of 145 g/m² in single line. The panels technological properties were evaluated according to the recommendations described in the relevant standards. As a result, we have: (i) the species basic densities was 0,42 g/cm³ for pinus, 0,37 g/cm³ for embaúba and 0,28 g/cm³ for paricá; (ii ) the yield of paricá venners was 80,03% and of embaúba venners was 46,73%; (iii) the highest amount of paricá and embaúba species venners were identified in class II and for pinus venners in class IV; (iv) the panels produced with Phenol-formaldehyde adhesive performed better bonding; (v) the panels made from embaúba wood and Phenol-formaldehyde adhesive, either neat or in combination with paricá wood, showed satisfactory technological properties for outdoor use; (vi) generally we found in this study that the embaúba with paricá and pure embaúba, as the best compositions, and the best adhesive for the panels was Phenol-formaldehyde because the tannin not performed well in the weight that was used.